Uncommon complication of feeding jejunostomy: A case report. Issue 5 (11th February 2019) - Basil, Tony; Sundaramurthi, Sudharsanan; Huthalm, Shankar; Goyal, Anuj; Dasarathan, Shanmugam; Dharanipragada, Kadambari
Abstract : Feeding jejunostomy is a common surgical procedure performed for patients who cannot take oral feeds. Although a minor procedure, it is not without complications. However, distal migration of the tube into the bowel is extremely rare. A 50‐year‐old woman with corrosive stricture of the esophagus because of feeding jejunostomy feeds presented with internal dislodgement of the feeding tube. Abdominal X‐ray and ultrasonogram could not locate the tube. On computed tomography, the feeding tube was found in the descending colon. She was managed conservatively, and the tube was expelled after three days. Internal dislodgement of tube usually does not produce any symptom. Computed tomography (CT) scan is diagnostic. Abstract : Distal migration of feeding jejunostomy tube into the bowel is an extremely rare complication. A 50‐year‐old woman with corrosive stricture of the esophagus on feeding jejunostomy feeds, presented with internal dislodgement of the feeding tube. On computed tomography the feeding tube was found in the descending colon. She was managed conservatively and the tube was expelled after 3 days. Internal dislodgement of tube usually does not produce any symptom and the patient requires surgical exploration only when they present with intestinal obstruction.